Single-crystal thin film material with hexagonal symmetry and preparation method and application thereof
Patent Information
- Application Number
- CN202510519800.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
但是,Sr3Al2O6牺牲层结构复杂,不易用于获得三重对称目标自支撑牺牲层体系,且稳定性较差
[0048](1)首次制备出六方对称性的单晶薄膜材料牺牲层,并通过该牺牲层制备相关六重对称性及三重对称性薄膜,为六方晶系氧化物研究提供了重要技术基础。
Smart Images

Figure CN122980030A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials. Specifically, this invention relates to a single-crystal thin film material with hexagonal symmetry, its preparation method, and its applications. Background Technology
[0002] In the field of two-dimensional materials, systems where van der Waals forces dominate interlayer interactions (such as graphene) can directly produce flexible self-supporting films through mechanical exfoliation. However, for complex oxides or semiconductor materials, the interlayer bonding strength is far greater than that of systems dominated by van der Waals forces due to the strong ion-covalent interactions between the epitaxial film and the substrate. This characteristic makes it impossible to directly fabricate flexible self-supporting films through mechanical exfoliation, thus leading to the development of solutions that utilize sacrificial layer transfer techniques to achieve material exfoliation.
[0003] Early studies mainly used SrRuO3 and La 1-x Sr x Materials such as MnO3 and MgO are used as sacrificial layers. However, these materials are limited by lattice constant mismatch or the need for strong acid / base solutions to dissolve the sacrificial layer (which may cause material damage), resulting in significant defects in the quality of the prepared films (see DM Paskiewicz, R. Sichel-Tissot, E. Karapetrova, et al., “Single-Crystalline SrRuO3 Nanomembranes: A Platform for Flexible Oxide Electronics”. Nano Lett. 16 (1) 534-542 (2016); SR Bakaul, C. Serrao, M. Lee, et al., “Single crystal functional oxides on silicon”. Nat. Commun. 7, 10547 (2016); and Y. Zhang, L. Shen, M. Liu, et al., “FlexibleQuasi-Two-Dimensional CoFe2O4 Epitaxial Thin Films for Continuous StrainTuning of Magnetic Properties”. ACS Nano (8) 8002-8009 (2017)).
[0004] This technological bottleneck has been overcome with the development of a novel water-soluble supercubic Sr3Al2O6 sacrificial layer. Due to its pseudocubic lattice parameters being highly compatible with the widely used SrTiO3 substrate, this material not only effectively solves the lattice mismatch problem but also allows for gentle exfoliation via aqueous solution (see D. Lu, DJ Baek, SS Hong, et al., “Synthesis of freestanding single-crystal perovskite films and heterostructures by etching of sacrificial water-soluble layers”. Nat. Mater. 15 1255-1260 (2016)). Based on this technology, the research team has successively discovered breakthrough properties in flexible thin film systems, including single-layer ferroelectric dynamics, superelastic ferroelectric films, strain-engineered ferroelectricity, precise control of polar nanodomains, and piezoelectric effect modulation. However, the Sr3Al2O6 sacrificial layer structure is complex, making it difficult to use for obtaining triple-symmetric target self-supporting sacrificial layer systems, and its stability is relatively poor. The Sr4Al2O7 sacrificial layer dissolves too quickly, is deliquescent in air, is difficult to store, and cannot be used for the preparation of non-in-situ self-supporting films (see Super-tetragonal Sr4Al2O7 as a sacrificial layer for high-integrity freestanding oxide membranes, Science 383, 388-394 (2024)).
[0005] Furthermore, existing research on sacrificial layers has significant limitations. Whether focusing on sacrificial layer materials or target thin films, the research focus is primarily on cubic and tetragonal crystal systems. There are currently no systematic research reports on hexagonal oxide sacrificial layers and their self-supporting thin films.
[0006] Therefore, there is an urgent need for a sacrificial layer material that is suitable for hexagonal and trigonal symmetry systems and is water-soluble. Furthermore, this material also needs to be air-stable. Summary of the Invention
[0007] The purpose of this invention is to provide a single-crystal thin film material with hexagonal symmetry. This material is suitable as a sacrificial layer in hexagonal and trigonal symmetry material systems and is water-soluble. Furthermore, this material also exhibits air stability.
[0008] Another object of the present invention is to provide a method for preparing the single-crystal thin film material with hexagonal symmetry of the present invention.
[0009] Another object of the present invention is to provide the use of the hexagonal symmetry single-crystal thin film material of the present invention as a sacrificial layer for the epitaxial preparation of self-supporting flexible thin films.
[0010] The above-mentioned objective of the present invention is achieved through the following technical solution.
[0011] In a first aspect, the present invention provides a single-crystal thin film material with hexagonal symmetry, wherein the single-crystal thin film material has the following chemical formula: MAl2O4; M is Ba, Ca or Sr.
[0012] Preferably, in the single-crystal thin film material with hexagonal symmetry described in this invention, using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material BaAl2O4, expressed in 2θ angles, has diffraction peaks at 20.28°, 41.14°, and 63.56°, with a 2θ angle measurement error of ±0.01°.
[0013] Preferably, in the single-crystal thin film material with hexagonal symmetry described in this invention, the single-crystal thin film material BaAl2O4 is hexagonal with space group P63.
[0014] Preferably, in the single-crystal thin film material with hexagonal symmetry described in this invention, using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material CaAl2O4, expressed in 2θ angles, has diffraction peaks at 21.78°, 44.43°, and 69.04°, with a 2θ angle measurement error of ±0.01°.
[0015] Preferably, in the single-crystal thin film material with hexagonal symmetry described in this invention, the single-crystal thin film material CaAl2O4 is a hexagonal crystal system with space group P63.
[0016] Preferably, in the hexagonal symmetry single-crystal thin film material of the present invention, using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material SrAl2O4, expressed in 2θ angle, has diffraction peaks at 21.06°, 42.93°, and 66.45°, and the 2θ angle measurement error is ±0.01°.
[0017] Preferably, in the single-crystal thin film material with hexagonal symmetry described in this invention, the single-crystal thin film material SrAl2O4 is hexagonal with space group P63.
[0018] Preferably, in the hexagonal symmetry single-crystal thin film material of the present invention, the single-crystal thin film material MAl2O4 (M is Ba, Ca or Sr) is water-soluble.
[0019] Secondly, the present invention provides a method for preparing the single-crystal thin film material with hexagonal symmetry of the present invention, which includes the following steps:
[0020] (1) Pre-sputtering the target material in a vacuum environment to remove impurities from the target material surface;
[0021] (2) Heating the substrate and controlling the oxygen partial pressure in the cavity, and adjusting the distance between the target and the substrate;
[0022] (3) Single-crystal thin film materials are prepared on the substrate using pulsed laser deposition technology or magnetron sputtering technology.
[0023] Preferably, in the method described in this invention, the substrate is an alumina substrate or a strontium titanate substrate.
[0024] Preferably, in the method described in this invention, the alumina substrate is oriented in the (0001) direction.
[0025] Preferably, in the method described in this invention, the strontium titanate substrate is oriented in the (111) direction.
[0026] Preferably, in the method described in this invention, the purity of the target material is 99% or higher.
[0027] This invention does not impose any particular limitation on the target material; conventional targets in the art can be used. For example, when preparing BaAl2O4 thin films, commercially available BaAl2O4 blocks can be used as the target material. These commercially available BaAl2O4 blocks are typically composite blocks containing BaO and Al2O3 in a 1:1 molar ratio. Similarly, when preparing CaAl2O4 thin films, commercially available CaAl2O4 blocks can be used as the target material. These commercially available CaAl2O4 blocks are typically composite blocks containing CaO and Al2O3 in a 1:1 molar ratio. When preparing SrAl2O4 thin films, commercially available SrAl2O4 blocks can be used as the target material. These commercially available SrAl2O4 blocks are typically composite blocks containing SrO and Al2O3 in a 1:1 molar ratio.
[0028] Preferably, in the method of the present invention, heating the substrate in step (2) is performed by heating the substrate to 650-850°C.
[0029] Preferably, in the method described in this invention, the control of the partial pressure of oxygen in the cavity in step (2) is carried out by controlling the partial pressure of oxygen in the cavity to 0.2-0.25 Torr.
[0030] Preferably, in the method described in this invention, the adjustment of the distance between the target and the substrate in step (2) is performed by adjusting the distance between the target and the substrate to 70-75 mm.
[0031] Preferably, in the method described in this invention, the laser energy of the pulsed laser deposition technique is 8-20 mJ / mm². 2 Preferably 10-12 mJ / mm 2 The deposition time is 30-60 minutes, preferably 40-50 minutes.
[0032] In a specific embodiment of the present invention, the method for preparing the single-crystal thin film material of the present invention may include the following steps:
[0033] (1) Pretreatment of substrate
[0034] The substrate was cleaned sequentially with acetone and ethanol, and then further cleaned using deionized ultrasonic technology. After drying, the substrate was placed in the sputtering chamber of the pulsed laser deposition system for later use.
[0035] (2) Pre-sputtering the target material in a vacuum environment to remove impurities from the target material surface;
[0036] (3) Heat the substrate to a certain temperature, control the oxygen partial pressure in the cavity, and adjust the distance between the target and the substrate;
[0037] (4) Then, pulsed laser deposition technology is used to deposit single-crystal thin film materials.
[0038] Thirdly, the present invention provides the use of the hexagonal symmetry single-crystal thin film material of the present invention as a sacrificial layer for the epitaxial preparation of self-supporting flexible thin films.
[0039] Preferably, in the application described in this invention, the self-supporting flexible film is insoluble in water.
[0040] Preferably, in the application described in this invention, the self-supporting flexible film has six-fold or three-fold symmetry.
[0041] Fourthly, the present invention provides a method for preparing a self-supporting flexible thin film, comprising the following steps:
[0042] (1) Depositing a self-supporting flexible thin film on the hexagonal symmetry single-crystal thin film material of the present invention;
[0043] (2) The hexagonal symmetric single-crystal thin film material used as a sacrificial layer is removed by water to obtain a self-supporting flexible film.
[0044] In a specific embodiment of the present invention, the method for preparing a self-supporting flexible thin film may include the following steps:
[0045] (1) Deposit a self-supporting flexible thin film (i.e., the target thin film) on the single crystal thin film material with hexagonal symmetry of the present invention.
[0046] (2) Polyethylene terephthalate is attached to the surface of the target film. The sample with polyethylene terephthalate attached is immersed in water to remove the single crystal film material with hexagonal symmetry (i.e., remove the sacrificial layer) and obtain a self-supporting flexible film (i.e., the target film).
[0047] The present invention has the following beneficial effects:
[0048] (1) For the first time, a sacrificial layer of hexagonal symmetry single crystal thin film material was prepared, and related six-fold symmetry and three-fold symmetry thin films were prepared through the sacrificial layer, which provided an important technical basis for the study of hexagonal oxides.
[0049] (2) Avoid material damage: Unlike the traditional non-water-soluble sacrificial layer that relies on acid / alkali corrosion in the prior art, the single-crystal thin film material of the present invention as the sacrificial layer can be dissolved in water, avoiding the damage to the target thin film material caused by the corrosion process and significantly improving the controllability of heterojunction preparation.
[0050] (3) Improve crystal quality: The unique hexagonal crystal structure of the single crystal thin film material with hexagonal symmetry of the present invention has excellent lattice matching characteristics with the target thin film material (such as square crystal system or trigonal symmetric material), which can greatly improve the crystal quality of the heterojunction interface and obtain the target film layer with high crystal integrity.
[0051] (4) Breakthrough in stability bottleneck: Compared with other known water-soluble sacrificial layer materials (such as Sr3Al2O6 and Sr4Al2O7), the single-crystal thin film material of the present invention as a sacrificial layer exhibits excellent chemical stability and can be stored for a long time in normal atmospheric environment. It can even support the subsequent secondary material growth on the surface of the sacrificial layer, thus breaking through the technical bottleneck of traditional water-soluble sacrificial layers that are difficult to balance long-term storage and controllable processing due to insufficient stability.
[0052] (5) Expanding the range of material preparation: The single-crystal thin film material with hexagonal symmetry of the present invention exhibits excellent chemical stability under various environmental high-temperature conditions. It can not only support the preparation of target materials under in-situ or ex-situ conditions, but also greatly expand the range of materials that can be prepared as self-supporting thin films, providing a foundation for the preparation of self-supporting thin films of a series of hexagonal material systems.
[0053] (6) Achieving cross-system integration innovation: With the same in-plane lattice symmetry, the single-crystal thin film material with hexagonal symmetry of the present invention is expected to achieve efficient heterogeneous integration with III-V group nitride semiconductors (such as GaN, InN, etc.) or two-dimensional materials (such as graphene, transition metal chalcogenides, etc.), breaking through the limitations of traditional device design and opening up new possibilities for innovative applications in fields such as flexible electronic systems and high-efficiency optoelectronic devices. Attached Figure Description
[0054] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:
[0055] Figure 1 The XRD pattern of the BaAl2O4 thin film prepared in Example 1 of the present invention is shown.
[0056] Figure 2 The STEM image of the BaAl2O4 thin film prepared in Example 1 of the present invention is shown.
[0057] Figure 3 The Rutherford backscattering test results of the BaAl2O4 thin film prepared in Example 1 of the present invention are shown.
[0058] Figure 4 The XRD pattern of the BaAl2O4 thin film prepared in Example 2 of the present invention is shown.
[0059] Figure 5 The XRD pattern of the CaAl2O4 thin film prepared in Example 3 of the present invention is shown.
[0060] Figure 6 The XRD pattern of the SrAl2O4 thin film prepared in Example 4 of the present invention is shown.
[0061] Figure 7 The XRD pattern of the BaAl2O4 film prepared in Example 1 of the present invention after dissolving in water is shown.
[0062] Figure 8 The XRD patterns of the CaAl2O4 and SrAl2O4 films prepared in Examples 3 and 4 of the present invention after dissolving in water are shown.
[0063] Figure 9 This shows an optical micrograph of the target thin film obtained in Example 5 of the present invention;
[0064] Figure 10 The stability test results of the BaAl2O4 thin film prepared in Example 1 of the present invention are shown. Detailed Implementation
[0065] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0066] Example 1
[0067] BaAl2O4 thin films were prepared on alumina substrates.
[0068] (1) Surface treatment of alumina substrate
[0069] The alumina substrate with orientation (0001) was cleaned sequentially with acetone and alcohol, and then treated with deionized ultrasonic technology. Then, the alumina substrate was rinsed in deionized water for 10 minutes, then taken out and dried, and placed in the sputtering chamber of the pulsed laser deposition system for later use.
[0070] (2) Pre-deposition treatment
[0071] First, a 99% pure barium aluminum oxide target (purchased from Hefei Kejing) was pre-sputtered in a vacuum environment to remove impurities from the target surface. Then, the alumina substrate was heated to 700°C; subsequently, the oxygen partial pressure in the cavity was controlled at 0.2 Torr, and the distance between the target and the substrate was adjusted to 75 mm.
[0072] (3) Preparation of BaAl2O4 thin film
[0073] Barium aluminum oxide thin films were deposited using pulsed laser deposition technology. The laser energy during the deposition process was 10 mJ / mm. 2 The deposition time was 45 min. The deposition process was observed using a high-energy reflection electron diffractometer. After deposition, the chamber was cooled to room temperature at a cooling rate of 7 °C / min to obtain a BaAl2O4 thin film on an alumina substrate.
[0074] Example 2
[0075] BaAl2O4 thin films were prepared on strontium titanate substrates.
[0076] (1) Surface treatment of strontium titanate substrate
[0077] The strontium titanate substrate with orientation (111) was cleaned sequentially with acetone and alcohol, and then treated with deionized ultrasonic technology. Then, the strontium titanate substrate was rinsed in deionized water for 10 minutes, then taken out and dried, and placed in the sputtering chamber of the pulsed laser deposition system for later use.
[0078] (2) Pre-deposition treatment
[0079] First, a 99% pure barium aluminum oxide target (purchased from Hefei Kejing) was pre-sputtered in a vacuum environment to remove impurities from the target surface. Then, the strontium titanate substrate was heated to 700°C; subsequently, the oxygen partial pressure in the chamber was controlled at 0.2 Torr, and the distance between the target and the substrate was adjusted to 75 mm.
[0080] (3) Preparation of BaAl2O4 thin film
[0081] Barium aluminum oxide thin films were deposited using pulsed laser deposition technology. The laser energy during the deposition process was 10 mJ / mm. 2The deposition time was 45 min. The deposition process was observed using a high-energy reflection electron diffractometer. After deposition, the chamber was cooled to room temperature at a cooling rate of 7 °C / min to obtain a BaAl2O4 thin film on a strontium titanate substrate.
[0082] Example 3
[0083] CaAl2O4 thin films were prepared on alumina substrates.
[0084] (1) Surface treatment of alumina substrate
[0085] The alumina substrate with orientation (0001) was cleaned sequentially with acetone and alcohol, and then treated with deionized ultrasonic technology. Then, the alumina substrate was rinsed in deionized water for 10 minutes, then taken out and dried, and placed in the sputtering chamber of the pulsed laser deposition system for later use.
[0086] (2) Pre-deposition treatment
[0087] First, a 99% pure calcium aluminum oxide target (purchased from Hefei Kejing) was pre-sputtered in a vacuum environment to remove impurities from the target surface. Then, the alumina substrate was heated to 700°C; subsequently, the oxygen partial pressure in the cavity was controlled at 0.2 Torr, and the distance between the target and the substrate was adjusted to 75 mm.
[0088] (3) Preparation of CaAl2O4 thin film
[0089] Calcium-aluminum oxide thin films were deposited using pulsed laser deposition technology. The laser energy during the deposition process was 10 mJ / mm. 2 The deposition time was 45 min. The deposition process was observed using a high-energy reflection electron diffractometer. After deposition, the chamber was cooled to room temperature at a cooling rate of 7 °C / min to obtain a CaAl₂O₄ thin film on an alumina substrate.
[0090] Example 4
[0091] Preparation of SrAl2O4 thin films on alumina substrates
[0092] (1) Surface treatment of alumina substrate
[0093] The alumina substrate with orientation (0001) was cleaned sequentially with acetone and alcohol, and then treated with deionized ultrasonic technology. Then, the alumina substrate was rinsed in deionized water for 10 minutes, then taken out and dried, and placed in the sputtering chamber of the pulsed laser deposition system for later use.
[0094] (2) Pre-deposition treatment
[0095] First, a 99% pure strontium aluminum oxide target (purchased from Hefei Kejing) was pre-sputtered in a vacuum environment to remove impurities from the target surface. Then, the alumina substrate was heated to 700°C; subsequently, the oxygen partial pressure in the cavity was controlled at 0.2 Torr, and the distance between the target and the substrate was adjusted to 75 mm.
[0096] (3) Preparation of SrAl2O4 thin film
[0097] Strontium aluminum oxide thin films were deposited using pulsed laser deposition technology. The laser energy during the deposition process was 10 mJ / mm. 2 The deposition time was 45 min. The deposition process was observed using a high-energy reflection electron diffractometer. After deposition, the chamber was cooled to room temperature at a cooling rate of 7 °C / min to obtain a SrAl2O4 thin film on an alumina substrate.
[0098] Example 5
[0099] The target film was prepared using BaAl2O4 film as a sacrificial layer.
[0100] (i) On the BaAl2O4 thin film on the alumina substrate obtained in step (3) of Example 1, a target thin film is further epitaxially grown; please refer to Table 1 below for the preparation process and the specific types of target thin films;
[0101] (ii) Remove the target film / BaAl2O4 film / alumina heterostructure, clean it, and attach polyethylene terephthalate. Immerse the sample with the attached polyethylene terephthalate in water to remove the BaAl2O4 film and obtain a flexible single crystal target film.
[0102] Table 1
[0103] Thin film types Substrate temperature (°C) Oxygen pressure (Pa) <![CDATA[Laser energy (mJ / mm 2 )]]> Target spacing (mm) Growth time (min) <![CDATA[YMnO3]]> 850 1.5 15 40 20 <![CDATA[In2O3]]> 700 7 13 45 20 <![CDATA[β-Ga2O3]]> 700 4 15 45 15 <![CDATA[LiCoO2]]> 750 20 13 40 15 <![CDATA[α-Fe2O3]]> 500 3 15 50 30 NiO 550 7 13 50 20
[0104] Performance Characterization
[0105] (I) Structural characterization of BaAl2O4 thin films
[0106] The physical properties of the BaAl2O4 thin film prepared in Example 1 were tested. The crystal orientation was analyzed by XRD diffraction, the crystal quality of the thin film was analyzed by transmission electron microscopy, and the atomic composition ratio was determined by Rutherford backscattering.
[0107] Figure 1 The XRD pattern of the BaAl2O4 thin film prepared in Example 1 of the present invention is shown; from Figure 1As can be seen, the obtained BaAl2O4 thin film exhibits a single orientation. Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal BaAl2O4 thin film, expressed in 2θ angles, shows diffraction peaks at 20.28°, 41.14°, and 63.56°, with a 2θ angle measurement error of ±0.01°. The BaAl2O4 thin film material belongs to the hexagonal crystal system with space group P63.
[0108] Figure 2 This shows a STEM image of the BaAl2O4 thin film prepared in Example 1 of the present invention; from Figure 2 As can be seen, the obtained BaAl2O4 thin film has a single orientation and regular atomic arrangement, exhibiting high crystallinity.
[0109] Figure 3 The Rutherford backscattering test results of the BaAl2O4 thin film prepared in Example 1 of the present invention are shown; from Figure 3 From this, we can conclude that the composition ratio of the BaAl2O4 film is Ba:Al:O≈1:2:4.
[0110] Figure 4 The XRD pattern of the BaAl2O4 thin film prepared in Example 2 of the present invention is shown; from Figure 4 As can be seen, the obtained BaAl2O4 thin film has a single orientation.
[0111] (II) Structural characterization of CaAl2O4 thin films
[0112] Figure 5 The XRD pattern of the CaAl2O4 thin film prepared in Example 3 of the present invention is shown; from Figure 5 As can be seen, the obtained CaAl₂O₄ thin film exhibits a single orientation. Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal CaAl₂O₄ thin film, expressed in 2θ angles, shows diffraction peaks at 21.78°, 44.43°, and 69.04°, with a 2θ angle measurement error of ±0.01°. The CaAl₂O₄ thin film material belongs to the hexagonal crystal system with space group P63.
[0113] (III) Structural characterization of SrAl2O4 thin films
[0114] Figure 6 The XRD pattern of the SrAl2O4 thin film prepared in Example 4 of the present invention is shown; from Figure 6As can be seen, the obtained SrAl₂O₄ thin film exhibits a single orientation. Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal SrAl₂O₄ thin film, expressed in 2θ angles, shows diffraction peaks at 21.06°, 42.93°, and 66.45°, with a 2θ angle measurement error of ±0.01°. The SrAl₂O₄ thin film material belongs to the hexagonal crystal system with space group P63.
[0115] (IV) Verification of the water solubility of BaAl2O4 thin films
[0116] The BaAl2O4 thin film prepared in Example 1 was placed in water, and the change in the lattice quality of the film was determined by XRD to determine its water solubility.
[0117] Figure 7 The XRD pattern of the BaAl2O4 thin film prepared in Example 1 of the present invention after dissolution in water is shown; from Figure 7 It can be seen that the BaAl2O4 film of the present invention has good water solubility and can be completely dissolved in water after 30 seconds.
[0118] (V) Verification of water solubility of CaAl2O4 and SrAl2O4 thin films
[0119] Figure 8 The XRD patterns of the CaAl2O4 and SrAl2O4 films prepared in Examples 3 and 4 of this invention after dissolution in water are shown; from Figure 8 It can be seen that the CaAl2O4 and SrAl2O4 films of the present invention have good water solubility, and can be completely dissolved in water after 10 seconds and 20 seconds, respectively.
[0120] (VI) Stability Testing
[0121] The BaAl2O4 thin film prepared in Example 1 was stored in air, and the mass change of the film was determined by XRD, XRR and AFM. It was then placed in extreme environments of high temperature, high oxygen pressure and high temperature ammonia, and its chemical stability was determined by XRD.
[0122] Figure 10 The stability test results of the BaAl2O4 thin film prepared in Example 1 of the present invention are shown.
[0123] Specifically, Figure 10 Figure a shows the XRD patterns of the BaAl2O4 thin film prepared in Example 1 of the present invention after being placed in air for different times. Figure 10 As can be seen, the XRD peak intensity of the BaAl2O4 film hardly changed after two weeks, indicating that the film can maintain lattice stability in air for a long time.
[0124] Figure 10b shows X-ray reflectance images of the BaAl2O4 thin film prepared in Example 1 of the present invention after being placed in air for different times. Figure 10 As can be seen from b, the density and thickness of the thin film crystals are not affected by air.
[0125] Figure 10 c-10d shows atomic force microscopy images of the BaAl2O4 thin film prepared in Example 1 of the present invention, immediately after preparation and after being placed in air for a period of time. Figure 10 As can be seen from c-10d, the surface of the film is very smooth and has not been corroded by water molecules in the air.
[0126] Figure 10 e shows the XRD pattern of the BaAl2O4 thin film prepared in Example 1 of the present invention under extreme conditions. Figure 10 As can be seen, the XRD peak intensity of the BaAl2O4 film hardly changes, indicating strong environmental stability.
Claims
1. A single-crystal thin film material with hexagonal symmetry, wherein, The single-crystal thin film material has the following chemical formula: MAl2O4; M is Ba, Ca or Sr.
2. The single-crystal thin film material with hexagonal symmetry according to claim 1, wherein, Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material BaAl2O4, expressed in 2θ angles, shows diffraction peaks at 20.28°, 41.14°, and 63.56°, with a 2θ angle measurement error of ±0.01°. Preferably, the single-crystal thin film material BaAl2O4 is hexagonal with space group P63.
3. The single-crystal thin film material with hexagonal symmetry according to claim 1, wherein, Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material CaAl2O4, expressed in 2θ angles, shows diffraction peaks at 21.78°, 44.43°, and 69.04°, with a 2θ angle measurement error of ±0.01°. Preferably, the single-crystal thin film material CaAl2O4 is hexagonal with space group P63.
4. The single-crystal thin film material with hexagonal symmetry according to claim 1, wherein, Using Cu target Kα diffraction, the X-ray powder diffraction pattern of the single-crystal thin film material SrAl2O4, expressed in 2θ angles, shows diffraction peaks at 21.06°, 42.93°, and 66.45°, with a 2θ angle measurement error of ±0.01°. Preferably, the single-crystal thin film material SrAl2O4 is hexagonal with space group P63.
5. The single-crystal thin film material with hexagonal symmetry according to claim 1, wherein, The single-crystal thin film material is water-soluble.
6. A method for preparing a single-crystal thin film material with hexagonal symmetry as described in any one of claims 1-5, comprising the following steps: (1) Pre-sputtering the target material in a vacuum environment to remove impurities from the target material surface; (2) Heating the substrate and controlling the oxygen partial pressure in the cavity, and adjusting the distance between the target and the substrate; (3) Single-crystal thin film materials are prepared on the substrate using pulsed laser deposition technology or magnetron sputtering technology.
7. The method according to claim 6, wherein, The substrate is an alumina substrate or a strontium titanate substrate; Preferably, the alumina substrate is oriented in the (0001) direction; Preferably, the strontium titanate substrate is oriented in the (111) direction; Preferably, the purity of the target material is 99% or higher; Preferably, heating the substrate in step (2) is performed by heating the substrate to 650-850°C; Preferably, the control of the partial pressure of oxygen in the chamber in step (2) is achieved by controlling the partial pressure of oxygen in the chamber to be between 0.2 and 0.25 Torr; Preferably, the adjustment of the distance between the target and the substrate in step (2) is performed by adjusting the distance between the target and the substrate to 70-75 mm; Preferably, the laser energy of the pulsed laser deposition technology is 8-20 mJ / mm². 2 The deposition time is 30-60 minutes.
8. The use of the single-crystal thin film material with hexagonal symmetry as any one of claims 1-5 as a sacrificial layer for epitaxial preparation of self-supporting flexible thin films.
9. The use according to claim 8, wherein, The self-supporting flexible film is insoluble in water; Preferably, the self-supporting flexible film has six-fold symmetry or three-fold symmetry.
10. A method for preparing a self-supporting flexible thin film, comprising the following steps: (1) Depositing a self-supporting flexible thin film on a single-crystal thin film material with hexagonal symmetry as described in any one of claims 1-5; (2) The hexagonal symmetric single-crystal thin film material used as a sacrificial layer is removed by water to obtain a self-supporting flexible film.